Zespół Metaboliczny cz. I: przegląd kryteriów rozpoznania zespołu metabolicznego = Metabolic Syndrome part I: overview of criteria of recognition of metabolic syndrome - Kalinowski, Paweł; Mianowana, Maryla (Journal of Education, Health and Sport, 2016)
Kalinowski Paweł, Mianowana Maryla. Zespół Metaboliczny cz. I: przegląd kryteriów rozpoznania zespołu metabolicznego = Metabolic Syndrome part I: overview of criteria of recognition of metabolic syndrome. Journal of Education, Health and Sport. 2016;6(3):211-226. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50678 http://ojs.ukw.edu.pl/index.php/johs/article/view/3496 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 23.03.2016. Zespół Metaboliczny cz. I: przegląd kryteriów rozpoznania zespołu metabolicznego Metabolic Syndrome part I: overview of criteria of recognition of metabolic syndrome Paweł Kalinowski1, Maryla Mianowana2 1. Samodzielna Pracownia Epidemiologii Uniwersytet Medyczny w Lublinie, ul. Staszica 4/6, 20-081 Lublin 2. Oddział Kardiologii – Pododdział Intensywnego Nadzoru Kardiologicznego, Wojewódzki Szpital Specjalistyczny im. Stefana Kardynała Wyszyńskiego, Al. Kraśnicka 100, 20-718 Lublin Słowa kluczowe: zespół metaboliczny, insulinooporność Key words: metabolic syndrome, insulin resistance Streszczenie Zespół Metaboliczny (ZM) po raz pierwszy opisano w 1981 roku. Od tego czasu eksperci międzynarodowych Towarzystw Naukowych zaproponowali wiele definicji tego zespołu. Celem pracy jest omówienie historii badań nad zespołem metabolicznym, definicji zespołu metabolicznego i jego składowych oraz wpływu zmian w kryteriach rozpoznawania na jego rozpowszechnienie w populacji. Pierwsza definicja zespołu metabolicznego została zaproponowana przez Światową Organizację Zdrowia (WHO) w 1998r. W odpowiedzi na kryteria zaproponowane przez WHO w 1999 roku ukazały się kryteria opracowane przez Europejską Grupę Badań Insulinooporności (EGIR), które nie zawierały mikroalbuminurii, jako elementu składowego, natomiast jako główne kryterium rozpoznania również wyodrębniono insulinooporność. W 2001 r. w Trzecim Raporcie Narodowego Programu Edukacji Cholesterolowej na temat wykrywania, oceny i leczenia hipercholesterolemii u osób dorosłych (NCEP-ATP III) ukazały się kolejne kryteria, które różniły się brakiem konieczności posiadania insulinooporności do rozpoznania zespołu metabolicznego, a przez co stały się proste w użyciu w praktyce klinicznej. Następne kryteria zostały opracowane przez Międzynarodową Federację Diabetologiczną (IDF). W 2009 r. IDF w porozumieniu z Amerykańskim Towarzystwem Kardiologicznym (AHA) i amerykańskim Narodowym Instytutem Serca, Płuc i Krwi (NHLBI) zaproponowała ujednoliconą definicję zespołu dla potrzeb wczesnej identyfikacji osób z grupy ryzyka chorób sercowo-naczyniowych. Wyniki badań nad rozpowszechnieniem zespołu metabolicznego wykazują różnice w populacjach w zależności od przyjętej definicji tego zespołu. Obecnie szacując jego częstość w populacjach na różnych kontynentach badacze posługują się kilkoma definicjami zespołu metabolicznego, by sprawdzić która z nich ma największą wartość prognostyczną rozwoju chorób sercowo-naczyniowych. Summary Metabolic syndrome (MS) was first described in 1981. Since then experts from international scientific societies have suggested many definitions of this disorder. The aim of the current study is to present the history of the research concerning metabolic syndrome, its definition, components and influence on the changes in the identification criteria for its distribution in the population. The first definition of metabolic syndrome was proposed by the World Health Organisation (WHO) in 1998. Following the criteria suggested by WHO in 1999, new ideas appeared, this time suggested by the European Group for the Study of Insulin Resistance (EGIR). They did not include microalbuminuria as one of its components, but indicated insulin resistance as a main criterion for the diagnosis of the syndrome. In 2001 the Third Report of the National Cholesterol Education Program (NCEP) Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (Adult Treatment Panel III, ATP III) presented another criterion, which differed in the lack of the need for insulin resistance in order to diagnose metabolic syndrome. Due to that fact they became far easier to use in clinical practice. The next criteria were devised by the International Diabetes Federation (IDF). In 2009 IDF, in agreement with the American Heart Association (AHA), and the American National Heart, Lung, and Blood Institute (NHLBI), proposed a unified definition of the syndrome for the purposes of the early identification of patients belonging to the cardiovascular disease risk group. The results of the research on the prevalence of metabolic syndrome show differences in populations depending on the definition of this syndrome. At present, when estimating its frequency in various populations, the researchers are utilising several definitions of metabolic syndrome in order to check which of them possesses the highest predictive value of cardiovascular disease development.